Project logistics: influential factors of transporting project cargo in the Balkan region - Herman, Benjamin (Mednarodno inovativno poslovanje, 2023)
Abnormal cargo will create abnormal problems and those require exceptional logistics solutions. This study delves into the complexities and challenges of transporting project cargo, explicitly focusing on items with extraordinary dimensions, weights, and shapes. Despite its small volume in global cargo flow, project cargo presents significant operational risks and contributions, particularly in the logistics sector. The research concentrates on the Balkan Peninsula, aiming to unravel the critical factors influencing project cargo transport and highlighting the challenges faced by industry experts.
Keywords: abnormal transport; Balkan region; balkanska regija; Delphi method; metoda Delph; nenormalni transport; project cargo; project logistics; projektna logistika; projektni tovor; Tovorni promet